A simple dynamic applied general equilibrium model of a small open economy: transitional dynamics and trade policy - Diao, Xinshen; Yeldan, A. Erinc; Roe, Terry L. (1998)
A dynamic general equilibrium model of a small open economy is presented to investigate the transition properties of out-of-steady state growth paths in response to trade policy shocks. With the application of the so-called Armingtonian commodity system of static CGE models, we quantify the nature of the transition path and the convergence speed towards the respective steady state under alternative parametrization of the substitution elasticities and of trade policy instruments.